2020
DOI: 10.1111/bcp.14578
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics, safety and dosing optimization of voriconazole in patients with liver dysfunction: A prospective observational study

Abstract: Voriconazole is a broad-spectrum antifungal agent for the treatment of invasive fungal infections. There is limited information about the pharmacokinetics and appropriate dosage of voriconazole in patients with liver dysfunction. This study aimed to explore the relationship between voriconazole trough concentration (C trough) and toxicity, identify the factors significantly associated with voriconazole pharmacokinetic parameters and propose an optimised voriconazole dosing regimen for patients with liver dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 43 publications
3
28
1
Order By: Relevance
“…A PPK analysis of patients with liver cirrhosis found that CYP2C19 genotypes strongly affected the CL of VRC 26 . However, the significant effect of CYP2C19 genotypes on the PK parameters of VRC in patients with liver dysfunction was not observed in two other PPK studies 25,34 . Similarly, the CYP2C19 phenotype (IM/PM vs. NM) was not identified as a significant covariate in the present study.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…A PPK analysis of patients with liver cirrhosis found that CYP2C19 genotypes strongly affected the CL of VRC 26 . However, the significant effect of CYP2C19 genotypes on the PK parameters of VRC in patients with liver dysfunction was not observed in two other PPK studies 25,34 . Similarly, the CYP2C19 phenotype (IM/PM vs. NM) was not identified as a significant covariate in the present study.…”
Section: Discussioncontrasting
confidence: 75%
“…However, dosing simulations in our present study showed that the intravenous VRC loading dose of 5 mg/kg q12h was adequate for Child‐Pugh class A/B and C patients to attain the C min target at 24 h with high probabilities (87.9% and 94.0%, respectively). Similarly, a lower loading dose of 200 mg q12h intravenously or orally was recommended for liver cirrhotic patients 24 and for total bilirubin (TBIL) −2 (51 μmol/L ≤ TBIL <171 μmol/L) and TBIL‐3 (TBIL ≥171 μmol/L) patients 25 . These studies indicated that patients with liver dysfunction required a reduced loading dose of intravenous VRC.…”
Section: Discussionmentioning
confidence: 99%
“…Voriconazole displays non-linear pharmacokinetic (PK) in adults and manifests extreme inter- and intra-individual PK variability in all patient populations, which are also associated with liver dysfunction, drug–drug interaction, etc. [ 18 , 19 , 20 , 21 ]. Although under the standard administration scheme, the voriconazole trough concentration [ 18 ], related to clinical efficacy, is distributed in the range of less than 0.2 mg/L to 12 mg/L, even exceptionally high (17.5 mg/L), leading to adverse reactions [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…VRCZ is mainly metabolised by CYP2C19 5. Liver dysfunction can reduce the plasma clearance of drugs because of the decrease in hepatic metabolism capacity or biliary excretion 6. Meanwhile, multiple factors are already known to be associated with variability in VRCZ serum concentrations including age, sex, weight and genetic polymorphism of the CYP2C19 enzyme,7–10 and create a challenge for clinicians to optimise VRCZ dosing regimens 11.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, multiple factors are already known to be associated with variability in VRCZ serum concentrations including age, sex, weight and genetic polymorphism of the CYP2C19 enzyme,7–10 and create a challenge for clinicians to optimise VRCZ dosing regimens 11. Hence, a number of studies have shown that therapeutic drug monitoring is useful in adjusting individualised dosing based on VRCZ plasma concentrations 5 6 12…”
Section: Introductionmentioning
confidence: 99%